Refractory Paraneoplastic Diarrhea Secondary to Adenocarcinoma of the Lung: A Case Report and Literature Review - Lauren Howdershelt; Michael J. Forte; Rahul G. Sangani (Case Reports in Critical Care)
Paraneoplastic diarrhea is a commonly described complication of gastrointestinal tract or endocrine malignancies. It is an extremely rare complication of lung adenocarcinoma, with only one previously reported case in the literature. A 46-year-old female with newly diagnosed stage IVb lung adenocarcinoma presented to our intensive care unit in hypovolemic shock with symptoms suggestive of diabetes insipidus (DI) as well as profuse large volume watery diarrhea. Exhaustive serological and microbiological workup revealed the diarrhea to be paraneoplasitc in nature. This case represents the second known case of paraneoplastic diarrhea secondary to lung adenocarcinoma. Clinicians should be aware of this rare phenomenon.